Characterization of bioactive compounds, antioxidants and antimicrobial properties of Allagoptera leucocalyx - Ayelen J. Camacho Crespo; Natalia Montellano Duran (Food Chemistry Advances)
Allagoptera leucocalyx is a non-studied tropical fruit distributed in the Bolivian Chiquitania region. This study aimed to investigate its bioactive compounds as well as its antioxidant and antimicrobial properties to encourage its consumption and explore potential applications in various industries. The bioactive compounds: polyphenols, flavonoids, and anthocyanins were determined by the Folin-Ciocalteu, AlCl3, and differential pH methods. Antioxidant activity was assessed by the DPPH● and ABTS● assays, while antimicrobial activity by turbidimetry and antibiogram. The highest results obtained revealed significant levels of polyphenols (209 ± 12 mg GAE/100 g), and flavonoids (7.9 ± 0.1 mg QE/100 g). Moreover, the fruit exhibit antioxidant activity (9.3 ± 0.2 μmol Trolox/g by ABTS● and 5.9 ± 0.2 μmol Trolox/g by DPPH●) and antimicrobial activity against Shigella sp. In conclusion, these promising findings suggest that this fruit could be utilized in the development of new products within the cosmetic, food, and pharmaceutical industries.